2012
DOI: 10.1007/s13197-012-0642-y
|View full text |Cite
|
Sign up to set email alerts
|

Modification of wheat starch with succinic acid/acetanhydride and azelaic acid/acetanhydride mixtures. II. Chemical and physical properties

Abstract: The aim of this research was to investigate the influence of modification with succinic acid/acetanhydride and azelaic acid/acetanhydride mixtures on chemical and physical properties of wheat starch. Starch was isolated from two wheat varieties and modified with mixtures of succinic acid and acetanhydride and azelaic acid and acetanhydride in 4, 6 and 8% (w/w). Total starch content, resistant starch content, degree of modification, changes in FT-IR spectra, colour, gel texture and freeze-thaw stability were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Starch chains combined and formed thick filaments, while water molecules condensed into ice crystals to form separate phases. After thawing, the ice was converted to water, which could be easily liberated from the polymer network during syneresis . The water loss rates of the oxidized starches were much higher than those of the native ones, as corroborated by other studies, which can probably be attributed to highly effective oxidization: the viscosity of the oxidized starch was too low to form a gel system after freezing.…”
Section: Resultssupporting
confidence: 92%
“…Starch chains combined and formed thick filaments, while water molecules condensed into ice crystals to form separate phases. After thawing, the ice was converted to water, which could be easily liberated from the polymer network during syneresis . The water loss rates of the oxidized starches were much higher than those of the native ones, as corroborated by other studies, which can probably be attributed to highly effective oxidization: the viscosity of the oxidized starch was too low to form a gel system after freezing.…”
Section: Resultssupporting
confidence: 92%
“…From a nutritional aspect, starch can be classified into three categories based on digestibility: rapidly digestible starch (RDS), slowly digestible starch (SDS), and resistant starch (RS) [5][6][7]. RS is starch that is not digested in the small intestine (of healthy individuals), and might therefore be partially fermented by the gut microflora in the large intestine [5,[7][8][9]. At present, different methods have been applied to prepare RS, including chemical, physical (hydrothermal), and enzymatic modification methods [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, until now, most of the works have been focused on corn, wheat, tapioca, sago and potato starches [ 3 , 6 , 7 , 8 , 9 ], few studies have been reported about the physicochemical properties of modified rice starch [ 4 , 10 ]. The objective of this study was to prepare the dual-modified rice starches (cross-linked oxidized starch and oxidized cross-linked starch), and comparatively investigate the physicochemical properties of native unmodified, cross-linked, oxidized and the two kind of dual-modified rice starch samples.…”
Section: Introductionmentioning
confidence: 99%